BUSINESS FEASIBILITY ANALYSIS CATFISH REARING CULTIVATION (CLARIAS GARIEPINUS) AT THE ROUND POND PT. TIMUR MANDIRI AKUAKULTUR - Surahmat, Djoko; Supriyadi, Bambang; Nugraha, Jefry Putri; Suseno, Dewi Alima Nostalia; Ergiyanti, Kharisma (Universitas Nusa Cendana, 2024)
Business feasibility analysis needs to be done for new businesses that want to open or are already running to provide information and an overview of what a catfish farming business looks like, whether it is still feasible or not to farmers. The purpose of this study is to determine the pattern of catfish enlargement farming business and determine the feasibility of catfish enlargement farming business from market and marketing aspects, technical aspects, management and organizational aspects, economic and social aspects, environmental aspects, and legality aspects, as well as knowing the financial feasibility of catfish enlargement farming business carried out by PT. Timur Mandiri Akuakultur. Financial feasibility analysis method using the method Net Present Value, Internal Rate of Return, Net B/Cand Payback Period. The results of the analysis on non-financial aspects show that the business is still feasible to run and develop. The results of the financial aspect analysis based on the value of the investment criteria obtained that the business is feasible to run and develop. Keywords: Feasibility Study; Cat Fish Enlargement Discretion; Venture Eligibility Analysis